University, Family Farming and Agroecological Transition: Systematization of an Extension Experience in Conservation Agriculture - Lorenzo, Daniel Rafael Vuelta; Rizo Mustelier, Miriela; Deroncelé, Kevin Chacón (New Countryside, 2026)
Food insecurity in contexts of socio-environmental vulnerability requires strategies that integrate sustainable production with the strengthening of local capacities. This article systematizes the experience of the Universidad de Oriente (Cuba) in supporting Family Farming (FF) systems for the adoption of Conservation Agriculture (CA) principles in the Santiago de Cuba municipality during the period 2010–2025. To critically reconstruct this experience and identify the main facilitators, obstacles, and lessons learned for the agroecological transition, a case study with a mixed approach was carried out, which included: (a) documentary review of 48 project reports, theses and training materials generated by the university; (b) application of a structured survey to farmers of 120 family plots in five localities (2025); and (c) conducting 15 semi-structured interviews with key producers, extension workers and academics (2023–2025). The results show that 65% of the plots adopt practices compatible with CA, mainly motivated by self-sufficiency (48.4%) and soil protection (45.1%). However, structural obstacles persist such as water scarcity (63.3%), lack of seeds (55.6%) and limitations in appropriate mechanization. The analysis reveals that university accompaniment, based on participatory action research approaches and dialogue of knowledge, has contributed to strengthening the self-esteem of producers, collective organization and the generation of contextualized knowledge. It is concluded that the university can play a relevant role in the agroecological transition when it acts as a facilitator of horizontal processes. The study provides lessons for designing university extension strategies aimed at food sovereignty in family farming contexts.